2020
DOI: 10.1136/bjophthalmol-2020-316111
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of retinal vessel diameter measurements from swept-source OCT angiography and adaptive optics ophthalmoscope

Abstract: Background/imsTo compare the retinal vessel diameter measurements obtained from the swept-source optical coherence tomography angiography (OCTA; Plex Elite 9000, Carl Zeiss Meditec, USA) and adaptive optics ophthalmoscope (AOO; RTX1, Imagine Eyes, France).MethodsFifteen healthy subjects, 67% women, mean age (SD) 30.87 (6.19) years, were imaged using OCTA and AOO by a single experienced operator on the same day. Each eye was scanned using two OCTA protocols (3×3 mm2 and 9×9 mm2) and two to five AOO scans (1.2×1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Retinal vessels measured from fundus photos are considerably larger in diameter than those obtained from OCTA [4]. Also, the diameters of retinal vessels measured with OCTA are in good agreement with the ground truth as obtained with adaptive optics ophthalmoscope [57]. Therefore, the lack of large vessel changes despite capillary changes suggests that microvascular alterations precede large vessel changes.…”
Section: Perfusion Density Of Large Vesselsmentioning
confidence: 73%
“…Retinal vessels measured from fundus photos are considerably larger in diameter than those obtained from OCTA [4]. Also, the diameters of retinal vessels measured with OCTA are in good agreement with the ground truth as obtained with adaptive optics ophthalmoscope [57]. Therefore, the lack of large vessel changes despite capillary changes suggests that microvascular alterations precede large vessel changes.…”
Section: Perfusion Density Of Large Vesselsmentioning
confidence: 73%
“…48 Vascular parameters were obtained from OCTA, which does not provide an actual quantification of blood flow but does provide a visualization of ocular perfusion, which has been shown to be a close approximation of vascular characteristics. 12 Assessments of structure–function relationships were limited to linear mixed models, 41 and other approaches were not considered. Only subjects from a single ethnicity were included in this study.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 OCT angiography (OCTA) is a recent technique 10 , 11 for the visualization of retinal perfusion to the level of capillaries. 12 In glaucoma, the usefulness of OCTA-based vascular metrics has been demonstrated in the discrimination of diseased eyes from healthy eyes. 13 15 Relating structural and, increasingly, vascular 16 25 changes with functional loss of vision in glaucoma is referred to as the structure–function relationship.…”
mentioning
confidence: 99%
“…The determination of the vessel diameter is an important feature to analyze retinal blood flow. It has been shown that the diameters of retinal vessels measured from OCTA scans were generally wider than with measurements obtained from adaptive optics ophthalmoscope (AOO) (100) or fundus photographs (101) regardless of scan protocols and vessel types. Reasons could be the oversampling rate of the OCTA system, the poorer lateral resolution compared with the AOO system or the effect of binarization (100).…”
Section: Optical Coherence Tomography Angiographymentioning
confidence: 99%